Synergistic multiple early therapy (SMET) for inflammatory diseases with pathogenic autoinflammatory feedback circuits. (25th May 2021) - McFadden, J.P.; Cunningham, L.S.; Ferguson, F.J.; Tziotzios, C.; McGrath, J.A.
Abstract : Linked Comment:  Marzano et al . Br J Dermatol 2021; 185 :133–140 .